The role of soil in the collapse of 18 piers of Hanshin Expressway in the Kobe earthquake. - Mylonakis, George
An investigation is presented of the collapse of a 630 m segment (Fukae section) of the elevated Hanshin Expressway during the 1995 Kobe earthquake. The earthquake has, from a geotechnical viewpoint, been associated with extensive liquefactions, lateral soil spreading, and damage to waterfront structures. Evidence is presented that soil?structure interaction (SSI) in non-liquefied ground played a detrimental role in the seismic performance of this major structure. The bridge consisted of single circular concrete piers monolithically connected to a concrete deck, founded on groups of 17 piles in layers of loose to dense sands and moderate to stiff clays. There were 18 spans in total, all of which suffered a spectacular pier failure and transverse overturning. Several factors associated with poor structural design have already been identified. The scope of this work is to extend the previous studies by investigating the role of soil in the collapse. The following issues are examined: (1) seismological and geotechnical information pertaining to the site; (2) free-field soil response; (3) response of foundation-superstructure system; (4) evaluation of results against earlier studies that did not consider SSI. Results indicate that the role of soil in the collapse was multiple: First, it modified the bedrock motion so that the frequency content of the resulting surface motion became disadvantageous for the particular structure. Second, the compliance of soil and foundation altered the vibrational characteristics of the bridge and moved it to a region of stronger response. Third, the compliance of the foundation increased the participation of the fundamental mode of the structure, inducing stronger response. It is shown that the increase in inelastic seismic demand in the piers may have exceeded 100% in comparison with piers fixed at the base. These conclusions contradict a widespread view of an always-beneficial role of seismic SSI.
Keywords: Bridge; Pier; Inelastic response; Numerical analysis; Piles; Soil structure interaction